Robust control system design advanced state space techniques - Tsui, Chia-Chi (Electrical engineering and electronics, 1996)
Unifies the two basic feedback structures of modern control theory. The work combines the design of state feedback control and its implementing controller, introducing an approach to state control system design. It offers end-of-chapter problem sets and partial solutions that help reinforce important concepts, as well as useful background mathematical information suitable for self-study.